Translation and validation of the Chinese version of medical maximizer-minimizer scale: a cross-sectional study - Lai, Fenghua; Pei, Ling; Yue, Shufan; Cao, Xiaopei; Xiao, Haipeng; Li, Yanbing; Li, Jin (BMJ open, 2021)
ObjectiveMedical overutilisation and underutilisation affect optimal healthcare. The Medical Maximizer-Minimizer Scale (MMS) was developed to assess individual medical maximising and minimising tendencies. Despite significant improvement in the healthcare system over the past four decades, no psychometric scales to examine treatment maximising and minimising preferences are available in China. This study aimed to translate the MMS into Chinese and examine its reliability and validity in a Chinese population.DesignThis cross-sectional study was conducted in December 2019 through an online survey panel.MethodsThe MMS was translated into a Chinese version (CN-MMS) using a forward–backward translation procedure. Next, a random online survey of the general population in China was conducted. Exploratory factor analysis (EFA) and confirmatory factor analysis were performed to examine the underlying factor structure of the CN-MMS. The internal consistency reliability of the scale was determined using Cronbach’s α coefficient and corrected item-total correlation. A multivariate linear regression analysis was used to examine associations between medical maximising and minimising preferences and demographic variables in the Chinese population.ResultsThis study included 984 participants aged 18–80 years. The CN-MMS retained 10 items, and the EFA supported a two-factor structure. The model fit for this two-factor structure of the CN-MMS was acceptable with χ2/df=3.7, comparative fit index=0.958, goodness-of-fit index=0.951, Tucker-Lewis Index=0.944 and root mean square error of approximation=0.074. The scale had a Cronbach’s α coefficient of 0.864, corrected item-total correlation of 0.451–0.667, and test–retest reliability of 0.815. Significant predictors of CN-MMS total score were nationality and household monthly income.ConclusionsThe CN-MMS showed satisfactory psychometric properties. Therefore, it can be used to investigate the individual medical maximising and minimising tendencies among the general Chinese population.